EUROPIUM SILICATE THIN FILMS FABRICATED BY RF MAGNETRON SPUTTERING AND THERMAL TREATMENT - Young Chul Shin; Eun Hong Kim; Tae Geun Kim (ASEAN Journal on Science and Technology for Development, 2007)
We report the fabrication and optical characteristics of europium silicate thin films. Layer structures of Eu2O3/SiOX/Si (100) were deposited by an rf-sputtering method and annealed at 1100°C by rapid thermal annealing (RTA). Two methods were used for the deposition of SiOX layer: One was deposited by sputtering using SiO2 target (Ar gas at a rate of 50 sccm) and the other was deposited by reactive sputtering using Si target (Ar gas at a rate of 45 sccm, with an O2 gas at a rate of 5 sccm). Photoluminescence peak at 430 nm was observed in the sample composed of SiOx  interlayer sputtered from SiO2 target. In comparison, PL peak at 570 nm was observed in the other sample, the SiOx layer of which was deposited by reactive sputtering from Si target. The compositional distributions of these samples were analyzed by X-ray photoelectron spectroscopy (XPS).